Relationship Between Economic Growth, Income Inequality and Poverty by Provinces in Indonesia: Panel Data Regression Approach - Suparman SUPARMAN (Indonesia Strategic Sustainability, 2022)
Researchers found that the decrease in income inequality affects the reduction of poverty through redistribution policies. This redistribution policy has also accelerated poverty reduction. In addition, the researcher found that the element of growth led to the achievement of poverty reduction in the long term. Researchers show that economic growth has the power to determine poverty reduction. The type of data in this study uses secondary data sourced from the Central Statistics Agency (BPS), namely Gross Regional Domestic Product (GRDP) at Constant Prices (ADHK) 2010, Number of Poor Populations, and Gini Ratio by Provinces in Indonesia during the period 2015-2020. The analytical method used is panel data regression using three forms, namely: CEM (common effect model), FEM (fixed effect model), and REM (random effect model). Based on the empirical findings using panel data regression, it can be concluded that the variables of economic growth (LOGPDRB) and income inequality (GIN) are consistent with various panel regression models as well as the common effect model (CEM), fixed effect model (FEM) and random effect. model (REM) has a positive effect on the number of poor people. This means that if the two variables increase, there will also be an increase or increase in the number of poor people according to the provinces in Indonesia.